2014
DOI: 10.5755/j01.ee.25.1.1847
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence on the Validity of CAPM: the Istanbul Stock Exchange Application

Abstract: As one of the most important models in the finance literature, the Capital Asset Pricing Model (CAPM) assumes the existence of a positive and linear relationship between the systematic risk and required rates of return on stocks. The model is extensively researched in the academia and frequently used in business world since its development half a century ago. Its popularity comes from the simplification it provides for the complex process of asset pricing by making the assumption that only one single factor af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…This approach was reflected in many studies. Research showed positive risk-return relationships which is consistent with the postulates of the CAPM (Bilgin & Basti, 2014;Fletcher, 2000;Jagannathan & Wang, 1996;Theriou, Aggelidis, Maditinos, & Šević, 2010;Trzpiot & Krężołek, 2006). The results obtained by Galagedera, Henry, & Silvapulle (2003) based on conditional regression illuminate often pessimistic conclusions regarding the equilibrium model.…”
Section: Literature Reviewsupporting
confidence: 78%
“…This approach was reflected in many studies. Research showed positive risk-return relationships which is consistent with the postulates of the CAPM (Bilgin & Basti, 2014;Fletcher, 2000;Jagannathan & Wang, 1996;Theriou, Aggelidis, Maditinos, & Šević, 2010;Trzpiot & Krężołek, 2006). The results obtained by Galagedera, Henry, & Silvapulle (2003) based on conditional regression illuminate often pessimistic conclusions regarding the equilibrium model.…”
Section: Literature Reviewsupporting
confidence: 78%
“…(66) had done research in Malaysia Stock Exchange and the result is consistent with our findings which linear reltionship between beta and return does exist. Some earlier researches such as (47,67,68) also support that beta and stock return has a linear relationship in their research. Expected return-beta relationship is linear also was being proven in the Amman Stock Exchange (49).…”
Section: Whole Period: Nonlinearitymentioning
confidence: 73%
“…Many studies prove an empirical result of there is a significant positively linkage between realised return and systematic risk as measured by beta, and there is linear relationship arise between risk and return (44)(45)(46). (47) and (48) also proved that there was a linear relationship between beta and return in Istanbul stock exchange. Expected return-beta relationship is linear also was being proven in the Amman Stock Exchange (49)In Australian Industrial equity market, cross sectional relationship between beta and average return is also in a situation of linear(50).…”
Section: Systematic Risk/ Beta (Independent Variable)mentioning
confidence: 95%
“…The risk of an asset can be measured by its responsiveness to that single factor. If the systematic risk and return relationship implied in this basic model could be validated in real world stock markets that would be a true revolution in finance (Bilgin and Basti, 2014).…”
Section: Literature Reviewmentioning
confidence: 98%